2017
DOI: 10.1111/evj.12781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of hysteroscopic hydrotubation for unexplained infertility in the mare

Abstract: This study revealed that hysteroscopic hydrotubation using saline improved pregnancy rates in mares in which oviductal blockage was suspected as a cause of unexplained subfertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This allows for evaluation of the internal os of the oviduct as well as patency. Subsequent studies showed that hydrotubation with flushing of the oviduct results in improved conception in mares with unexplained infertility (Inoue and Sekiguchi 2018;. After hysteroscopic guided catheterization and flushing 26 of 28 mares became pregnant.…”
Section: Diagnostic and Therapeutic Uses Of Hysteroscopymentioning
confidence: 99%
“…This allows for evaluation of the internal os of the oviduct as well as patency. Subsequent studies showed that hydrotubation with flushing of the oviduct results in improved conception in mares with unexplained infertility (Inoue and Sekiguchi 2018;. After hysteroscopic guided catheterization and flushing 26 of 28 mares became pregnant.…”
Section: Diagnostic and Therapeutic Uses Of Hysteroscopymentioning
confidence: 99%
“…A further impediment to sperm–oocyte interaction and, in particular, the subsequent descent of the fertilised embryo into the uterus, is occlusion of the ampulla by accumulations of inspissated follicular fluid, unfertilised oocytes or degenerate embryos which do not secrete the prostaglandin E2 required to initiate their descent into the uterus. Administering PGE2 onto the surface of the oviduct laparoscopically is one way to salvage fertility in mares presumed to be suffering from oviductal occlusion 6 ; recently, endoscope‐guided flushing of the oviducts via the uterus (“hysteroscopic hydrotubation”) was shown to be a valid alternative treatment for re‐establishing oviductal patency in mares, while avoiding the risks of laparoscopy 7 . Of course, oocyte recovery for oocyte transfer or fertilisation by intracytoplasmic sperm injection (ICSI) is also a way to salvage fertility in the case of oviductal occlusion.…”
Section: Ensuring Spermatozoa and Oocyte Meet At The Right Time And Right Placementioning
confidence: 99%
“…Administering PGE2 onto the surface of the oviduct laparoscopically is one way to salvage fertility in mares presumed to be suffering from oviductal occlusion 6 ; recently, endoscope-guided flushing of the oviducts via the uterus ("hysteroscopic hydrotubation") was shown to be a valid alternative treatment for re-establishing oviductal patency in mares, while avoiding the risks of laparoscopy. 7 Of course, oocyte recovery for oocyte transfer or fertilisation by intracytoplasmic sperm injection (ICSI) is also a way to salvage fertility in the case of oviductal occlusion.…”
Section: En Suring S Permatozoa and Oo C Y Te Mee T At The Ri G Ht Time And Ri G Ht Pl Acementioning
confidence: 99%
“…Since there are risks associated with entering the peritoneal cavity, the recently described success of hysteroscopic hydrotubation (i.e. retrograde flushing of the oviducts via the uterotubal junction) for resolving unexplained infertility may make it an attractive alternative. In sport horses, by contrast, OPU‐ICSI is rapidly becoming a first‐line approach to tackle sub‐fertility, irrespective of the cause.…”
mentioning
confidence: 99%